Insiders, Outsiders, and Nominal Wage Contracts - Gottfries, Nils (Journal of Political Economy, 1992)
While the consequences of nominal wage contracts have been rather thoroughly analyzed, there is no generally accepted theory of why such contracts prevail. In this paper I argue that the distinction between insiders and outsiders is important for understanding nominal wage contracts. Since most employment fluctuations take the form of fluctuations in hiring, insiders are normally not affected by them. Since prices are primarily determined by costs, demand shocks have small effects on real wages. Thus insiders have little incentive to change to more complicated contracts. With rigid nominal wages, nominal demand shocks have large effects on the employment opportunities of outsiders, but outsiders have little influence on labor contracts.